2018
DOI: 10.2139/ssrn.3146968
|View full text |Cite
|
Sign up to set email alerts
|

Financialization and Industrial Policies in Japan and Korea Evolving Complementarities and Loss of Institutional Capabilities

Abstract: The purpose of this article is to analyze the revival of industrial policies from the late 2000s in Japan and Korea and their limitations. Our approach has two major characteristics. First, we adopt the perspective of historical institutionalism to focus on the relation between IPs and financial systems and study their evolution over the last 40 years. Second, by mobilizing the concepts of institutional complementarities and hierarchy, we discuss the limits of this revival in a context of liberalized financial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…To be sure, there is a case to be made that when viewed in total, liberalization was an essential ingredient in ensuring Korea's continued economic expansion in the post-developmental state era (see Pirie 2008, 1-16). Furthermore, the dilemmas emerging from the ideological legacies discussed here mirror institutional incongruities that coincided with liberalization and continued to muddle state economic initiatives for decades to come (Lechevalier, Debanes, and Shin 2017). All this said, the chief point of emphasis here is that segyehwa's policies-regardless of their technical meritswere forced to grapple with the ideological legacies imparted from the Park era.…”
Section: In Search Of the 'Global Mind'mentioning
confidence: 87%
“…To be sure, there is a case to be made that when viewed in total, liberalization was an essential ingredient in ensuring Korea's continued economic expansion in the post-developmental state era (see Pirie 2008, 1-16). Furthermore, the dilemmas emerging from the ideological legacies discussed here mirror institutional incongruities that coincided with liberalization and continued to muddle state economic initiatives for decades to come (Lechevalier, Debanes, and Shin 2017). All this said, the chief point of emphasis here is that segyehwa's policies-regardless of their technical meritswere forced to grapple with the ideological legacies imparted from the Park era.…”
Section: In Search Of the 'Global Mind'mentioning
confidence: 87%
“…This required greater efforts to cooperate with other ministries, including with the then Ministry of education (Elder, 2003). Moreover, the liberalisation of the economy increased the decentralisation and compartmentalisation of STI policies among different ministries, which led to significant efforts to "re-coordinate the economy" (Lechevalier et al, 2016).…”
Section: Policy Coordinationmentioning
confidence: 99%
“…Political economic approach defines institutions as "political compromises among different interest groups that form socio-political coalitions to advance their interests" (Lechevalier et al, 2016, p. 6). It has been very recently that Yamada & Hirano (2015) as well as Lechevalier et al (2016) and Jackson (2016) have demonstrated the merits of applying political economic theory to the issue of intensified SV pursuit in Japan and its connection to labor deregulation. While their analysis is yet preliminary, current research incorporates and tests the view about the pursuit of SV being a political project aimed at power accumulation (Amable, 2016).…”
Section: Research Operationalization: Shareholder Value and Nonregulamentioning
confidence: 99%